Agent-based social networking for mobile user. (16th November 2010) - Belavic, Rebeka; Basuga, Marko; Podobnik, Vedran; Petric, Ana; , Ignac Lovrek
Nowadays, social network services play an important role in users' everyday lives. This is especially emphasised in lives of users that belong to Generation Y. Young people often communicate and share various personal information with their family, friends or colleagues through virtual communities that are based on social relations. By introducing social networking concept into the mobile network domain, proliferation and availability of social networking services could be notably expanded. This paper presents an agent-based social network for users in the mobile network domain. The presented social network enables mobile users to define and customise their social relationships with other users, as well as to use those relationships for planning and managing group events. Additionally, users can also create and use wish lists.